Grb10, a Positive, Stimulatory Signaling Adapter in Platelet-Derived Growth Factor BB-, Insulin-Like Growth Factor I-, and Insulin-Mediated Mitogenesis - Wang, Jian (American Society for Microbiology, 1999)
Grb10 has been described as a cellular partner of several receptor tyrosine kinases, including the insulin receptor (IR) and the insulin-like growth factor I (IGF-I) receptor (IGF-IR). Its cellular role is still unclear and a positive as well as an inhibitory role in mitogenesis depending on the cell context has been implicated. We have tested other mitogenic receptor tyrosine kinases as putative Grb10 partners and have identified the activated forms of platelet-derived growth factor (PDGF) receptor β (PDGFRβ), hepatocyte growth factor receptor (Met), and fibroblast growth factor receptor as candidates. We have mapped Y771 as a PDFGRβ site that is involved in the association with Grb10 via its SH2 domain. We have further investigated the putative role of Grb10 in mitogenesis with four independent experimental strategies and found that all consistently suggested a role as a positive, stimulatory signaling adaptor in normal fibroblasts. (i) Complete Grb10 expression from cDNA with an ecdysone-regulated transient expression system stimulated PDGF-BB-, IGF-I, and insulin- but not epidermal growth factor (EGF)-induced DNA synthesis in an ecdysone dose-responsive fashion. (ii) Microinjection of the (dominant-negative) Grb10 SH2 domain interfered with PDGF-BB- and insulin-induced DNA synthesis. (iii) Alternative experiments were based on cell-permeable fusion peptides with the Drosophila antennapedia homeodomain which effectively traverse the plasma membrane of cultured cells. A cell-permeable Grb10 SH2 domain similarly interfered with PDGF-BB-, IGF-I-, and insulin-induced DNA synthesis. In contrast, a cell-permeable Grb10 Pro-rich putative SH3 domain binding region interfered with IGF-I- and insulin- but not with PDGF-BB- or EGF-induced DNA synthesis. (iv) Transient overexpression of complete Grb10 increased whereas cell-permeable Grb10 SH2 domain fusion peptides substantially decreased the cell proliferation rate (as measured by cell numbers) in normal fibroblasts. These experimental strategies independently suggest that Grb10 functions as a positive, stimulatory, mitogenic signaling adapter in PDGF-BB, IGF-I, and insulin action. This function appears to involve the Grb10 SH2 domain, a novel sequence termed BPS, and the Pro-rich putative SH3 domain binding region in IGF-I- and insulin-mediated mitogenesis. In contrast, PDGF-BB-mediated mitogenesis appears to depend on the SH2 but not on the Pro-rich region and may involve other, unidentified Grb10 domains. Distinct protein domains may help to define specific Grb10 functions in different signaling pathways.